Electroacupuncture Attenuates Visceral Hypersensitivity by Inhibiting JAK2/STAT3 Signaling Pathway in the Descending Pain Modulation System - Wan, Juan; Ding, Yi; Tahir, Adnan H.; Shah, Manoj K.; Janyaro, Habibullah; Li, Xiaojing; Zhong, Juming; Vodyanoy, Vitaly; Ding, Mingxing (Frontiers in Neuroscience, 2017)
Electroacupuncture (EA) has been used for treating visceral hypersensitivity (VH). However, the underlying molecular mechanism remains unclear. This study was aim to testify the effect of EA on ileitis-provoked VH, and to confirm whether EA attenuates VH through Janus kinase 2 (JAK2)/ signal transducers and activators of transcription 3 (STAT3) signaling pathway in the periaqueductal gray (PAG)-the rostral ventromedial medulla (RVM)-the spinal cord dorsal horn (SCDH) axis. Methods: Goats were anaesthetized and laparotomized for injecting 2,4,6-trinitro-benzene-sulfonic acid (TNBS)-ethanol solution (30mg TNBS dissolved in 40% ethanol) into the ileal wall to induce VH. EA was treated for 30 min from day 7, then every three days for six times. VH was assessed by visceromotor response (VMR) and pain behavior response to 20, 40, 60, 80 and 100 mmHg colorectal distension pressures at day 7, 10, 13, 16, 19 and 22. The spinal cord in the eleventh thoracic vertebra and the brain were collected at day 22. The protein and mRNA levels of IL-6, JAK2 and STAT3 in the SCDH were detected with western blot and qPCR, respectively. The distribution of these substances was observed with immunohistochemistry in the ventrolateral PAG (vlPAG), RVM (mainly the nucleus raphe magnus, NRM), SCDH, the nucleus tractus solitaries (NTS) and the dorsal motor nucleus of vagi (DMV). Results: Goats administered with TNBS-ethanol solution showed diarrhea, enhanced VMR and pain behavior response, and increased IL-6, phosphorylated JAK2 and STAT3 (pJAK2 and pSTAT3) in the vlPAG, NRM, NTS and DMV, and their protein and mRNA levels in the SCDH. EA relieved diarrhea, VMR and pain behavior response, decreased IL-6, pJAK2 and pSTAT3 levels in the vlPAG, NRM, SCDH, NTS and DMV except for pSTAT3 in the DMV, but did not affect mRNA level of these three substances in the SCDH. Conclusion: EA attenuates VH probably through inhibiting JAK2/STAT3 signaling pathway in the PAG-RVM-SCDH axis.